Detection Of Waterborne Pathogens in Drinking Water in Ajdabiya City - Haniyeh Ahmed Mohamed Argiah (African Journal of Advanced Pure and Applied Sciences, 2025)
Waterborne pathogens pose a major health risk in both developed and developing countries. Providing quality domestic water for the community is crucial. The aim of this study was to examine various drinking water sources in several areas of Ajdabiya to ensure they are free of contamination and fit for drinking. Community health was evaluated to determine the level of water pollution. Method: Four water samples were collected: 21 from the public network (river water), 23 from bottled water (mineral water), 4 from well water, and 2 from rainwater. Total coliforms were analyzed, Escherichia coli and Streptococcus were analyzed in water samples. The household survey included questions about the city’s residential area, the main source of drinking water at home, the type of drinking water tanks, the frequency of chlorine addition to drinking water, the frequency of cleaning drinking water tanks, and whether the drinking water had been tested. Has a family member become ill after drinking the water? What type of illness? Do you know the sources of water pollution? Are you aware of the risks of water pollution? In your opinion, what is the best solution to address the problem of drinking water pollution? The results of the tests were compared to the permissible limits set by the World Health Organization finding that coliform was 100%, Escherichia coli was 73.9%, and streptococcus was 23.9% of the water samples. E. coli concentration levels were high. The household survey results revealed that water pollution was highest in the eastern and northern parts of the city among residents using the public water network. Pollution levels were highest in underground tanks, followed by rooftop tanks. Pollution levels were lowest among those who cleaned their tanks twice a year. Chlorinated water contains a much lower number of colony-forming units (CFU) per 100 ml of water sample. In conclusion, improper sewage disposal is a primary factor contributing to water pollution in the city, followed by pollution from contaminated water tanks and a lack of awareness of water purification and sterilization. There is an urgent need to take emergency steps to stop further deterioration of water quality and to improve the existing water quality to protect the population from the spread of waterborne diseases.